2011
DOI: 10.1090/s0025-5718-2011-02490-7
|View full text |Cite
|
Sign up to set email alerts
|

The infrastructure of a global field of arbitrary unit rank

Abstract: Abstract. In this paper, we show a general way to interpret the infrastructure of a global field of arbitrary unit rank. This interpretation generalizes the prior concepts of the giant-step operation and f -representations, and makes it possible to relate the infrastructure to the (Arakelov) divisor class group of the global field. In the case of global function fields, we present results that establish that effective implementation of the presented methods is indeed possible, and we show how Shanks' baby-step… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…For the sake of completeness, we now describe the reduction in more detail. The infrastructure of a number field is isomorphic to a torus T = R d /M, where M is a fullrank lattice in R d and the coefficients of all non-trivial vectors of M are transcendental numbers [Fon11]. This forces one to work with approximations, which is ultimately responsible for the poor performance when the dimension d increases.…”
Section: Relevance Of Lattice Generation To Quantum Algorithms and Qumentioning
confidence: 99%
“…For the sake of completeness, we now describe the reduction in more detail. The infrastructure of a number field is isomorphic to a torus T = R d /M, where M is a fullrank lattice in R d and the coefficients of all non-trivial vectors of M are transcendental numbers [Fon11]. This forces one to work with approximations, which is ultimately responsible for the poor performance when the dimension d increases.…”
Section: Relevance Of Lattice Generation To Quantum Algorithms and Qumentioning
confidence: 99%
“…The result is a cleaner and simpler ideal arithmetic, avoiding the need for numerical approximations as discussed in the previous section. Moreover, interestingly, integer distances make it possible to provide an explicit and effective embedding of the principal infrastructure into a finite cyclic group whose order is the regulator, as was discovered independently by Fontein [12] and Mireles Morales [22]. Such an embedding into a finite cyclic group does not exist in the number field setting, although embedding the infrastructure into an infinite cyclic group is possible (see [20]).…”
Section: Beyond Infrastructure In Real Quadratic Fieldsmentioning
confidence: 99%
“…Fontein [17] showed that it is possible to compute in a finite abelian group which he denotes Rep f * (ᏻ) and which is isomorphic to ‫ޚ‬ n / . We discuss his approach in the next section.…”
Section: Computing Efficiently In the Unit Groupmentioning
confidence: 99%
“…Minima and reduced ideals in function fields. We now give the definitions of minima and reduced ideals and define Rep f * (ᏻ) (see [17]). In the following, by an ideal of ᏻ we will always mean a fractional ideal of ᏻ.…”
Section: Amentioning
confidence: 99%
See 1 more Smart Citation